ANALISIS KUALITAS AIR DI HUTAN MANGROVE PESISIR NEGERI AMAHAI KABUPATEN MALUKU TENGAH - Ridwan Wailisa; Jusmy D. Putuhena; Fanny Soselisa (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2022)
This study aims to analyze the air quality of mangrove forests on the coast of Amahai, Central Maluku Regency, including DO, salinity, temperature, pH, TDS, BOD and NH4. Data were analyzed directly in the field and in the laboratory. Measurement of air quality is divided into 3 (three) research locations. Each location represents the condition and character of the environment, namely near the estuary, middle and far from the estuary. The water quality of each location was analyzed descriptively. The results showed that the condition of the coastal waters of Amahai State at high tide had a range (DO between 101.8 – 109.2 mg/l, TDS between 101.8 – 109.2 mm/l, temperature between 29.5 – 30.0 OC, salinity between 3.9 – 4.5, pH between 6.3 – 6.7, NH4 between 0.005 – 0.008 mg/l and BOD between 3 – 3.9 mg/l) compared to low tide conditions with DO quality range between 5.7 – 6.3 mg/l, temperature between 29.0 -29.5 OC, salinity between 3.2 - 4 , pH between 6.3 - 6.9, NH4 between 0.006 - 0.008 mg /l and BOD between 3.2 – 3.7 mg/l). Overall the measurement results are still within the permitted quality standard limits. The air quality index calculation shows DO and TDS parameters in good category, pH and BOD in fairly good category, while DO and salinity parameters are in poor condition. The calculation of the Pollution Index for each parameter is based on the Decree of the Minister of the Environment No. 51 of 2004 at three sampling points, Mangrove Tourism Places, Estuary/River and Amahai Settlement. for each parameter Good Status for parameters DO, salinity, temperature, pH, TDS, BOD and NH4.